Impact specimen geometry on T23 and TP347HFG steels behaviour during steam oxidation at harsh conditions - Dudziak, T.; Lukaszewicz, Mikolaj; Simms, Nigel J.; Nicholls, John R. (Taylor and Francis, 2016)
Ferritic T23 steel and austenitic TP347HFG steel have been studied with an emphasis on understanding the impact of specimen geometry on their steam oxidation behaviour. The selected materials were tested over a wide range of temperatures from 600 to 750°C. The tests were carried out in 100% steam conditions for 1000 hours. The tests indicated that the ‘curved-shaped’ specimens show slower mass gain, scale ticking and void nucleation rates than ‘bridge-shaped’ specimens (with flat and convex surfaces combined). Furthermore, a bridge TP347HFG sample showed the formation of lower amount of flaky oxide at 750°C.
Keywords: Steam oxidation; Steels; Energy sector; Shape; Ferritic; Austenitic; Oxidation